ESG Performance and Firm Value: Evidence from the Indonesian Sharia Stock Index - Aziizah, Febriana Putri Nur; Fanani, Sunan (Jurnal Ekonomi Syariah Teori dan Terapan, 2025)
This study analyzes the effect of Environmental, Social, and Governance (ESG) on firm value among companies listed in the Indonesia Sharia Stock Index (ISSI) during 2018–2023, both partially and simultaneously. ESG is relevant in Islamic investing as it aligns with the principles of justice, sustainability, and ethical business. Firm value is measured using Tobin’s Q, while ESG is assessed through ESG Score, Environmental, Social, and Governance scores obtained from Bloomberg. The study employs panel data regression using the Random Effect Model, with size and leverage as control variables. The results show that both ESG Score and environmental performance have a significant negative effect on firm value, indicating that better ESG and environmental performance may reduce firm value. Social and governance scores have no significant impact. These findings suggest that ESG implementation in Indonesia remains suboptimal and does not yet reflect the Islamic economic principles of benefit and sustainability. Further research is needed to analyze companies that meet the Sharia Securities List (DES), compare firms with and without ESG practices, and examine specific sectors that may contribute most to the decline in firm value due to ESG. This is crucial for understanding ESG effectiveness in Indonesia's Islamic capital market.